THE ROLE OF EDUCATION, SCIENCE AND PRODUCTION INTEGRATION PROCESS IN THE DEVELOPMENT OF UNIVERSITY RESEARCH AND INNOVATION POTENTIAL - Valeriy A. Anishchenko (Высшее образование в России)
The article deals with the issues of integration of education, science and production by the example of Kumertau Branch of Orenburg State University. The author proposes the ways to gain an optimal solution to arrange an effective interaction between employers and university through the system of supplementary professional training in Kumertau Branch.